2021
DOI: 10.3390/ijerph182312548
|View full text |Cite
|
Sign up to set email alerts
|

Insecure Employment Contracts during the COVID-19 Pandemic and the Need for Participation in Policy Making

Abstract: Job security influences the ability of nurses to provide high-quality nursing care. The Iranian health system has always faced nursing shortages, and the COVID-19 pandemic has worsened this situation. Although nurses have been labelled ‘heroes’ across the globe, many of them have been hired using insecure employment contracts. This commentary aims to describe issues surrounding job contracts for Iranian nurses during the COVID-19 pandemic and discusses how the current situation can be improved. Iranian nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Another study found that the nursing students' motivation to finish their program of study decreased with the number of semesters [ 61 ]. The shortage of nursing in the Iranian health system is critical, and even nurses with low grades can be easily employed in the Iranian health system [ 62 ]. It seems that nursing students' motivation may decrease with the number of semesters by the thought that nursing is a safe job.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that the nursing students' motivation to finish their program of study decreased with the number of semesters [ 61 ]. The shortage of nursing in the Iranian health system is critical, and even nurses with low grades can be easily employed in the Iranian health system [ 62 ]. It seems that nursing students' motivation may decrease with the number of semesters by the thought that nursing is a safe job.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that nursing students' motivation may decrease with the number of semesters by the thought that nursing is a safe job. In addition, a feeling of the large salary gap between nurses and physicians in Iran [ 62 ] could lead to a decrease in the motivation of Iranian nursing students over time.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of immigration requests from nurses has increased by 300% during the pandemic. 4 Those who remained in the country have worked day and night through multiple waves of COVID-19, hoping for permanent elimination of the virus and a better, healthier future.…”
Section: The Future Of Iran's Health Workforcementioning
confidence: 99%
“…Except for the permanent staff and those with longterm employment contracts, the rest of the health workforce was recruited in hospitals using various forms of employment that did not ensure any future job security, including 89-day contracts and a volunteer workforce with small payments. 4 Moreover, national laws needed to support medical staff were only partially implemented or not implemented at all. The ratio of nurses and nurse aid staff per hospital bed is approximately 0•8-1•0 per bed 6 (compared with the standard of 3•0 nurses per bed and 4•0 nurse aid staff per bed).…”
Section: The Future Of Iran's Health Workforcementioning
confidence: 99%
“…Abuse of care workers negatively impacts their physical and mental wellbeing, reduces job satisfaction, increases burnout, absenteeism and turnover, and reduces retention at the organisational level [19,[38][39][40][41][42][43]. Such experiences ultimately impact care quality, safety and efficiency [18,[44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%